STUDY THE LIFE CYCLE AND SOME OTHER CHARACTERIZED OF BLASTOCYSTIS HOMINIS: (SUBJECT REVIEW) - Rajaa Mosa Ismai; Ahmed Hamad Saleh; Hyam Jamal Ibrahim (Scholar Express Journals, 2022)
With an incidence that often exceeds 5% among all people in wealthy countries and that can reach 3060% in developing countries, Blastocystis sp. is one of the few gastrointestinal parasites. Interestingly, the only stramenopile capable of infecting people is Blastocystis sp. Blastocystis sp. has four main morphological forms that have been identified in stool samples or in vitro cultures: vacuolar, granular, amoeboid, and cyst forms. Numerous instances of B. hominis from feces and the human gut suggest that the organism can take on other forms. This genus is widespread around the world and is frequently the most frequently reported normal gastrointestinal protozoan in children, adults, and even infants.
Keywords: Blastocystis hominis; Intestinal parasites; Vacuolar form; Blastocystosis